MÔ PHỎNG, TÍNH TOÁN DÒNG CHẢY VÀ QUÁ TRÌNH TRUYỀN TẢI, KHUẾCH TÁN NƯỚC THẢI Ô NHIỄM TRONG HỒ - Thắng, Nguyễn Tất (Vietnam Journal of Earth Sciences, 2011)
Simulation and calculation of flow and pollutant transport in lake The paper presents researched results on simulation and calculation of wind-induced flow and pollutant transport in West Lake - Hanoi using the non-commercial EFDC computer code developed under the support of the Environmental Protection Agency (EPA) of the US. The West Lake model, input/output data processing, and the presentation of calculated results have been done using the pre/post processor EFDC_Explorer (EE), WEB version. Flow and pollutant transport simulation is for a period in dry season (e.g. calculation with wind data of the first part of December 2010). The simulated results of wind-induced current in the lake give us an interesting idea of the detailed circulation of the water in the lake, a subject that has not yet been experimentally studied till now. The results of pollutant transport simulation firmly confirm, and clearly explain the reason of the difference in water quality between the southern part of the lake and the northern one, which has been found in field observations. Hopefully, high resolution results of this research and further results of simulations of the future West Lake development plans will contribute useful information to Hanoi city authorities. Concurrently this research confirms the promise in using the EFDC free code to study other practical problems in Vietnam.